Avaliação da maturidade da saúde digital no Brasil: uma análise sob a ótica do Global Digital Health Index e do modelo de inovação Hélice Quíntupla - Adalton da Silva Ramos Júnior (2021)
Corresponding to the use of information and communication technologies in the health area, the modality called digital health is configured as a milestone of technological advancement and employment applied to a sector characterized by many challenges inherent to the demand and supply of care services. Through digital health, the aim is to help promote health and increase the population's self-care, support professionals in clinical analysis and decisions, in addition to providing improvements in the management of health services, and reducing the sector's expenses. The movement to implement digital health has taken place progressively, but at a different pace around the world. In this sense, maturity assessment models help to identify the stage of development of national initiatives and strategies. Considering the above and taking into account the Brazilian reality, the present work had as general objective to carry out a diagnosis of the stage of maturity of digital health in Brazil, in order to offer support for the establishment of actions involving the government, the academy, the industry and civil society in the expansion of these services in the country, and to analyze the evaluation structure used from the perspective of subsystems of the Quintuple Helix innovation model. The assessment was carried out through the application of the Global Digital Health Index (GDHI) model, a structure with indicators distributed in seven dimensions of analysis and five stages of maturity, designed based on guidelines from the World Health Organization along with the International Telecommunications Union. Complementarily, an analysis of the GDHI was carried out from the perspective of the Quintuple Helix innovation and knowledge model, in order to verify the scope of the GDHI before the educational, economic, political, public, and natural environment subsystems. The adopted methodology proved to be adequate, indicating that Brazil is in a digital health scenario in transition, from an initial stage to an intermediate stage of maturity. There is a national perspective still focused on planning and organization scopes and not very effective in terms of implementation and expansion. As for the GDHI analysis, considering the Quintuple Helix model, there was a concentration of indicators related to the political subsystem, with aspects being proposed to compose the digital health maturity assessment, especially in the public and natural environment subsystems. Thus, in addition to identifying the maturity stage of digital health in Brazil, this study contributes to increasing the scope of the Quintuple Helix innovation model, based on the use of its subsystems in the context of digital transformations in the health area.